By elimination, it means that we should apply algebraic operations so we find the value of one variable. So first, lets multiply the first equation by 5. We get
![5\cdot(2x-3y)=5\cdot-5\text{ = 10x-15y = -25}](https://img.qammunity.org/2023/formulas/mathematics/college/hgyigxc6njirgn2i1kwr32vq9sw2kdjktt.png)
Now, lets multiply by 2 the second equation
![2\cdot(5x+2y)\text{ = 16}\cdot2\text{ = 10x+4y=32}](https://img.qammunity.org/2023/formulas/mathematics/college/y3uv3v4nwy695rj7fdfj8p08lcq2wm561b.png)
With this two equations, lets subtract the second equation from the first equation
![10x+4y-(10x-15y)\text{ = 32-(-25)}](https://img.qammunity.org/2023/formulas/mathematics/college/46g8u8q6qbmbk697d956slwh6rtuhzjxp9.png)
We get
![19y\text{ = 57}](https://img.qammunity.org/2023/formulas/mathematics/college/wylxnkfmvvuagxav3pwrriv7copzr6mkg4.png)
If we divide y by 19 we get
![y=(57)/(19)=3](https://img.qammunity.org/2023/formulas/mathematics/college/b8eil842umsua1xaz7ai1bg9hyiphgfxc2.png)
Now, using this value in the second equation we get
![5x+2\cdot3\text{ = 16 }=5x+6](https://img.qammunity.org/2023/formulas/mathematics/college/xbnig2y9qoy843sxuhsk1hdtdvf3n2d6ja.png)
If we subtract 6 on both sides, we get
![16-6\text{ = 5x = 10}](https://img.qammunity.org/2023/formulas/mathematics/college/4f3zbehnhtdhfpykgqv4nnmf7if9criri7.png)
Finally, we divide by 5 on both sides and we get
![x=(10)/(5)=2](https://img.qammunity.org/2023/formulas/mathematics/college/2ozjxmp4z09ydtf1xjiqan4qhllwi5jehp.png)